Semantic approach to food marketing: the influence of sustainable development narratives on the Ukrainian market - Anna Burkovska; Alla Burkovska (Agricultural and Resource Economics)
Purpose. The purpose of the study is to evaluate the application of the semantic approach in food marketing by establishing the impact of narratives of sustainable development on the promotion of agricultural products on the market of Ukraine.